Research Progress on Metabolic Reprogramming in Cancer Cachexia and Intervention with Traditional Chinese Medicine Formulations - Liu, Donghu; Shen, Xiaoying; Ren, Qinyou (Journal of Contemporary Medical Practice, 2025)
As a common complication of cancer, cachexia has a high prevalence and significantly affects patients’ quality of life and prognosis. It is closely associated with sarcopenia, leading to decreased muscle mass and dysfunction. The metabolic mechanism of cachexia sarcopenia is complex, involving glucose, lipid, amino acid, nucleotide metabolism and other aspects. Traditional Chinese Medicine believes that sarcopenia belongs to the category of ‘flaccidity syndrome’, while tumor cachexia sarcopenia belongs to asthenic fatigue and thinness. The occurrence and development of this condition are believed to be caused by a deficiency of vital qi, which is thought to be related to a corresponding decline in the function of the spleen, liver, kidney and viscera function. With regard to the treatment of ailments, Traditional Chinese Medicine is founded upon the principle of invigorating the spleen, combined with the methods of benefiting qi and stomach, soothing liver and promoting qi, detoxifying and resolving masses, nourishing yin and activating blood circulation to alleviate the symptoms of sarcopenia. At present, Chinese patent medicines such as Kanglaite Injection, Kangai Injection, Zilongjin Tablets and Traditional Chinese Medicine compound have made progress in improving the symptoms of cachexia and sarcopenia, regulating metabolic mechanism and improving the quality of life. These studies provide new reference and ideas for the treatment of cancer cachexia and sarcopenia with Traditional Chinese Medicine.